First- and second-order effects of consumers’ institutional logics on firm–consumer relationships: A cross-market comparative analysis - Singh, Jagdip; Lentz, Patrick; Nijssen, Edwin J (Journal of International Business Studies, 2011)
Consumers’ conceptions of a market's institutional logic affect mechanisms of firm–consumer relationships, but are generally neglected in comparative studies of international marketing. This study bridges institutional and relationship marketing theories to examine two questions: do consumers hold meaningful mental models of a market's institutional logics, and do these mental models explain differentiated patterns of market relationships across international contexts? Building on contract-relational duality, we develop a market-level construct for capturing consumers’ socially constructed mental models for the institutional logics of market action. We theorize that differences in consumers’ institutional logics will influence both their evaluation of a firm's capabilities (first-order effect) and the degree to which they reward a firm through their commitment (second-order effect). These bridging predictions are tested using data from the insurance industry across three international markets. Our results show that the German insurance market is located in the relatively high contracts–low relational quadrant, whereas the US and Dutch markets are both located in the relatively low contracts – high relational quadrant. Our results also suggest that consumer commitment conforms to a principle of alignment such that commitment accrues to providers who align their capabilities with consumers’ prevalent institutional logics of the market, and penalizes those who deviate from it.